Autostygmatyzacja osób z niepełnosprawnością wzrokową - GŁADYSZEWSKA-CYLULKO, JOANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Joanna Gładyszewska-Cylulko, Self-stigma in the visually impaired, Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 179–193. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.11 The blind and visually impaired are one of the groups prone to stigma. Stigma imposed by social environment may lead to self-stigma, that is expressing negative opinions about oneself as a result of the carried sigma. Self-stigma usually develops in three stages: first the stigmatised person realizes that they have been stereotyped, then they accept the stereotype and finally apply it to themselves. Thus, to develop selfstigma, the person has to be aware that they are perceived by the society in a stereotypical way (a blind person is usually perceived as passive, dependent and reliant on other people’s help), accept it and acknowledge themselves that this is their real image. Not every visually impaired person is will develop self-stigma. The article presents selected factors and preventive measures that may reduce the risk of self-stigma.